1997
DOI: 10.1097/00004728-199701000-00025
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Breast in the Differential Diagnosis of Mastitis Versus Inflammatory Carcinoma and Follow-Up

Abstract: While breast MR cannot currently be used definitively to distinguish inflammatory carcinoma from mastitis, the differences in dynamic enhancement may prove to be useful in follow-up of presumed mastitis in problematic cases. If after biopsy the diagnosis remains unclear, breast MR may help to (a) demonstrate the success of the antibiotic treatment and (b) diagnose coexisting or confounding inflammatory carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 11 publications
3
42
0
3
Order By: Relevance
“…Unfortunately, these findings were non-specific and similar to findings for carcinoma. MRI features of non-puerperal mastitis described in the published literature are scarce [7,13,14]. These reports state that non-puerperal mastitis has a wide spectrum of appearances, such as a ring-like enhancement, intensively enhancing irregular mass and focal homogeneous enhancing masses, which are all consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Unfortunately, these findings were non-specific and similar to findings for carcinoma. MRI features of non-puerperal mastitis described in the published literature are scarce [7,13,14]. These reports state that non-puerperal mastitis has a wide spectrum of appearances, such as a ring-like enhancement, intensively enhancing irregular mass and focal homogeneous enhancing masses, which are all consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Lesions were mammographically undetectable in 6 of 25 females, possibly because of an overlying dense mammary gland pattern observed in most females. With mammography, two patients in our study showed nipple retraction, and one showed skin thickening in the mammary areola, which is more commonly observed in inflammatory breast carcinoma or invasive carcinoma [7][8][9]. The ultrasound manifestations of non-puerperal mastitis varied.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations